(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To study the acute toxicity and effects of the dried extract of "clearing and purifying" on the general health and kidney function of experimental animals . Research subjects and methods: Acute toxicity of the dried extract was assessed in white mice using the Litchfield–Wilcoxon method. The effects of the extract on general health and kidney function were evaluated in 50 white rats with chronic kidney disease induced by 5/6 nephrectomy. The rats were divided into 5 groups: TTGT-1 (administered the dried extract at a dose of 0.735 g/kg/day), TTGT-2 (1.47 g/kg/day), the model group (administered distilled water), the reference group (enalapril 10 mg/kg/day), and the surgical control group (no kidney removal, administered distilled water). The treatment lasted 60 days. Evaluation parameters included general condition, serum urea and creatinine levels, kidney weight, and renal histopathology before and after treatment. Results: The maximum dose of 30 g/kg (23.6 times the expected therapeutic dose) caused no mortality or signs of toxicity. After 60 days, serum urea and creatinine levels in the TTGT-1 and TTGT-2 groups significantly decreased compared with baseline and the model group (p<0.01). Conclude: The dried extract "transforms purity into impurity". Achieved safety in acute toxicity testing. The dried extract "ascends the pure and descends the impure" Doses of 0.735 g/kg/24h and 1.47 g/kg/24h reduced serum urea and creatinine levels in experimentally resected white rats with chronic kidney disease.